ROTASI KERJA DITINJAU DARI WORK-LIFE BALANCE PADA ANGGOTA SATBRIMOB POLDA JATENG - Pratama Yuda Gumelar; Alice Zellawati (IMAGE, 2024)
Work-life balance is very important for organizations and individuals. One of the factors that influences work-life balance is job rotation. The aim of this research is to empirically test and analyze the relationship between job rotation and work-life balance. The Work-life balance variable is measured using a Likert scale which is based on dimensions according to Fisher (2009), namely Demands which consists of WIPL (Work Interference with Personal Life), PLIW (Personal Life with Work Interference), and Resources which consists of WEPL (Work Enhancement of Personal Life), PLEW (Personal Life Enhancement of Work). Job rotation variables are measured using a Likert scale which is based on dimensions based on Edwan's (2013) theory, namely experience, knowledge, needs, work performance and responsibility. The population in this study were members of the Central Java Police Mobile Brigade Staff, totaling 140 members, using a saturated sampling technique. The results of this research prove that there is a positive and very significant correlation between work rotation and work-life balance as shown by the correlation value rs = +0.725 (p = 0.000). The work rotation coefficient is 54.7% and the remaining 45.3%. Keywords : Work-life balance, Work Rotation.